Tingkat Pemahaman Materi Pendidikan Jasmani Kelas XI Terhadap Pembelajaran Tatap Muka Terbatas - Arif Saputro, Febianto; Prayogi, Fatih (Universitas Singaperbangsa, 2022)
This study aims to determine the level of understanding of grade 11 students in physical education learning materials. Data was collected using a survey technique (questionnaire) given to students. From the results of the analysis of research data, namely the level of understanding of physical education material for grade 11 to face-to-face learning transitions, it shows the lack of understanding of students obtained in learning materials, so that face-to-face learning transitions to date are not optimal. Therefore, the school and teachers revise the transitional face-to-face learning system and learning materials that will be given to students.